Molecular genetic characteristic of dinucleotide microsatellite loci in parthenogenetic lizards Darevskia unisexualis - Omelchenko, A. V; Korchagin, V. I; Sevast'yanova, G. A; Ryskov, A. P; Tokarskaya, O. N (Russian journal of genetics, 2009)
In the present study, the first molecular genetic investigation of dinucleotide (GT) n microsatellite loci in parthenogenetic lizards Darevskia unisexualis was performed. New polymorphic locus, Du214, (GenBank Ac. No. EU252542) was identified and characterized in detail. It was demonstrated that allele of this locus differed in the size and structure of microsatellite locus, as well as in point mutations, the combinations of which enabled the isolation of stabile fixed double nucleotide substitutions A-A (alleles 2 and 4) and G-T (alleles 1, 3, 5, and 6). Double nucleotide substitutions described were also identified in the orthlogous loci of the parental species genomes, D. raddei (G-T) and D. valentine (A-A). Based on the analysis of allele distribution pattern at this locus in all populations of parthenospecies D. unisexualis, mathematic model was elaborated and realized. Using this model, frequencies of allelic variants for all populations of the species of interest were calculated and population genetic structure of D. unisexualis was characterized. Genetic contribution of each population to the species gene pool was determined. The data obtained demonstrated that microsatellite variation was one of the factors of clonal and genetic diversity of a parthenospecies.